2018
DOI: 10.1097/bsd.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

Blood Loss Trends and Financial Implications in Adolescent Idiopathic Scoliosis

Abstract: Several blood conservation strategies, including use of ICS, exist to minimize the consequences of blood loss. Routine use of preoperative type and cross may be avoided except in cases where significant blood loss is anticipated-that is adolescent male individuals, those with a lower body mass index and in whom a longer surgical time is anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…4,10 The present study also found that male patients have more HBL which is consistent with previous studies. 4,10,18,19 The reason why male patients have more HBL may be related to the greater height and weight and higher blood volume. These factors together with higher Hb content led to more serious blood loss when male patients lose the same volume of blood.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 The present study also found that male patients have more HBL which is consistent with previous studies. 4,10,18,19 The reason why male patients have more HBL may be related to the greater height and weight and higher blood volume. These factors together with higher Hb content led to more serious blood loss when male patients lose the same volume of blood.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with high expected blood loss, such as those undergoing surgery for adolescent idiopathic scoliosis, ICS has been found to be cost-neutral compared to allogeneic blood transfusion. 99 Most studies have found ICS to have a very low complication profile, though at least one study has reported acute kidney injury in the setting of ICS transfusion. 100…”
Section: Intraoperative Cell Salvagementioning
confidence: 99%
“…There is some data to suggest that EBL is higher in male patients compared to female patients with AIS. 14 The sex distribution between cohorts may have been a confounding variable.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a previous retrospective cohort study in a similar target population, 14 we anticipated EBL/level in the proposed study would be 48 mL/level (AE30) in the experimental group and 72 mL/level (AE28) in the control group. Based on a two-sided, alpha level of 0.05, we determined that a sample size of 62 subjects (31 subjects per group) would provide 90% power to detect a 24 mL/level reduction in blood loss with USBS when compared with the osteotome.…”
Section: Sample Size and Stopping Criteriamentioning
confidence: 99%